Cutaneous Manifestations of Infection in the Immunocompromised Host - Grossman, Marc E.; Fox, Lindy P.; Kovarik, Carrie; Rosenbach, Misha (Springer New York : Imprint: Springer, 2012)
The updated second edition  of Cutaneous Manifestations of Infection in the Immunocompromised Host is an invaluable reference for physicians and ancillary medical professionals involved in the care of patients with impaired immune systems due to cancer, chemotherapy, systemic steroids and other immunosuppressive drugs, HIV/AIDS or  organ transplantation. This volume  will help you recognize skin lesions  and diagnose their infectious cause. Textbook features include: ·         Over 350 color images demonstrating pathognomonic, atypical, rare and routine skin lesions ·         Tables for differential diagnosis of different skin lesions in the immunocompromised host ·         Complete coverage of infectious pathogens with the patterns of infection and the likely causes in different clinical settings (HIV/AIDS versus solid organ transplantation versus neutropenia post-chemotherapy versus bone marrow recovery post hematopoietic stem cell transplantation ) ·         New chapter discussing the role of viruses causing malignancies with cutaneous signs in the immunocompromised patient   Written by dermatologists, the new edition is an indispensable  diagnostic tool intended for use by all clinicians  who care for immunocompromised patients.  .